Peran Audit Internal dalam Meningkatkan Keandalan Pengelolaan Aset Tetap melalui Efektivitas Pengendalian Internal pada Entitas Bisnis - Anggun Suryani Hasmal; Atika Syahra; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the role of internal audit in enhancing the reliability of fixed asset management through the effectiveness of internal control within business entities. Fixed assets hold strategic value and directly influence operational sustainability, thereby requiring accurate systems of supervision, record-keeping, and reporting. Various studies indicate that weaknesses in documentation, physical oversight, and inconsistent procedural implementation often become sources of unreliable asset information. Through a comprehensive literature review, this research identifies that internal audit plays a significant role in assessing and strengthening the effectiveness of internal control by conducting compliance testing, asset verification, and identifying risks in asset recording. The reviewed literature demonstrates a mutually reinforcing relationship between internal audit and internal control, in which effective controls support audit quality, while internal audit ensures that control procedures are consistently implemented. Moreover, internal audit provides operational recommendations that enhance the accuracy, security, and accountability of fixed asset management. This study affirms that internal audit is a crucial element of corporate governance, contributing directly to the reliability of financial reporting and the long-term effectiveness of asset management.